GESTIÓN DE LOS RIESGOS QUÍMICOS PARA DISMINUIR DAÑOS EN LA SALUD DE LOS TRABAJADORES EN UNA TIENDA DE PINTURA - GONZÁLEZ RUEDA, JOSTYN ANDRE (2025)
This research focused on the problem of prolonged exposure to chemicals during the execution of different processes in a paint store, with the objective of developing proposals to optimize chemical risk management.